Air Quality of Bursa: Temporal and Spatial Evaluation of PM10, PM2.5, NO2 and SO2 Pollutants Using IDW Geostatistical Technique - Duygu Arıkan İspir; Ferruh Yıldız (Doğal Afetler ve Çevre Dergisi)
One of the most significant environmental issues is air pollution. Human health is negatively impacted by this issue in addition to the environment. In this study, spatial and temporal analysis of particulate matter 10 (PM10), particulate matter 2.5 (PM2.5), sulfur dioxide (SO2) and nitrogen dioxide (NO2) pollutants for 2022 was conducted within the provincial borders of Bursa, Turkey. The monthly and seasonal air pollution maps have been generated using 24-hour measurements obtained from air quality monitoring stations within the city. Data for PM10, PM2.5, SO2, and NO2 were utilized in the creation of these maps. The pollution maps were analyzed based on the criteria outlined in the World Health Organization (WHO) report, as well as the limit values set by the European Union and the national regulations. According to the results obtained, the amount of pollutants in summer is lower than in winter. While PM10 was on average 39.32 μg/m³ in the summer months, it exceeded the national legislation by 3.09% in the winter. When evaluated during the average summer season, the concentrations of PM2.5 and SO2 were observed to be 19.29 μg/m³ and 5.82 μg/m³, respectively. In contrast, during the winter season, the concentrations were found to be 47.30 μg/m³ for PM2.5 and 11.07 μg/m³ for SO2. There is no legal limit for PM2.5 in national legislation. SO2 was found to be below the specified legal regulations. While NO2 was on average 25.13 μg/m³ in the summer months, it exceeded the national legislation by 9.74% in the winter. The main sources of pollutants in the region were examined and according to the findings, factors such as the city being an industrial zone and high traffic density increased the pollutants. The results of this investigation show that air pollution poses a significant issue in Bursa.